Attachment theory and research new directions and emerging themes - Simpson, Jeffry A.; Rholes, W. Steven (William Steven) (The Guilford Press, 2015)
"This volume showcases the latest theoretical and empirical work from some of the top scholars in attachment. Extending classic themes and describing important new applications, the book examines several ways in which attachment processes help explain how people think, feel, and behave in different situations and at different stages in the life cycle. Topics include the effects of early experiences on adult relationships; new developments in neuroscience and genetics; attachment orientations and parenting; connections between attachment and psychopathology, as well as health outcomes; and the relationship of attachment theory and processes to clinical interventions. Key Words/Subject Areas: attachment research, attachment security, attachment theory, couple interventions, developmental psychology, dyadic regulation process, emotion, parenting, psychopathology, relationships, romantic functioning, romantic attachment Audience: Researchers and students in social, developmental, personality, and clinical psychology. Serves as a primary or supplemental text in advanced undergraduate or graduate courses on attachment, close relationships, interpersonal processes, and family relationships "-- Provided by publisher.